Organoleptic Test of Jelly Candy Made from Kawa Leaf Water - Daneswara, Kadek Ryan; Trisdayanti, Ni Putu Eka (PT FORMOSA CENDEKIA GLOBAL, 2024)
The purpose of this study was to determine and describe the quality of jelly candy made from kawa leaf water in terms of organoleptic in terms of taste, aroma, texture and color. The lack of utilization of coffee leaves by the community is due to the lack of public knowledge about how to utilize coffee leaves. This study uses a qualitative descriptive method to determine the quality of jelly candy made from kawa leaf water, using data collection techniques: experiments, documentation, organoleptic tests, questionnaires and Likert scales to get the best results from jelly candy made from kawa leaf water. The overall results of jelly candy made from kawa leaf water received an average rating of 89.75% with very good interpretation criteria. This study can be continued with testing to determine the nutritional content of jelly candy made from kawa leaf water.